A Discourse Analysis of Hegemonic Masculinity on TV Advertisements - Amelia Yuli Astuti; Annisa Idafini Ardi (Jurnal Ilmiah Langue and Parole, 2018)
This research entitled “A Discourse Analysis of Hegemonic Masculinity on TV Advertisements” aims to identify cohesion, context and coherence when research the hegemonic masculinity on TV advertisement, identify representations of masculinity on TV advertisement, and analyze hegemonic masculinity realized on TV advertisement.This research uses discourse analysis approach. Where, the researcher used descriptive research method, which aims to create descriptions, as well as describe the data naturally from TV advertisement about hegemonic masculinity. And in collecting data researcher use techniques see, hear and record, then classified and analyzed.In this research found 5 of 5 categories by Halliday and Hasan (1976) are: reference, substitution, ellipsis, conjunction and lexical cohesion. Then 8 categories of context in advertisement according to Cook (1992) are: substance, music and picture, paralanguage, situation, a joint text, intertext, participants. Furthermore according to Reinhart (1980) that coherence is categorized into 3 categories namely: connectedness, consistency and relevant. Finally,the discovery of masculinity and hegemonic masculinity based on the concept of Connel (1995) on TV advertisement. Based on the results of this research, researcher concluded that the advertisement on TV, which where the advertisement of male products on TV contained full of messages in the form of hegemonic masculinity in it.